Icariside II prevents hypertensive heart disease by alleviating endoplasmic reticulum stress via the PERK/ATF-4/CHOP signalling pathway in spontaneously hypertensive rats. (20th November 2018) - Wu, Yuting; Yue, Yun; Fu, Shu; Li, Yeli; Wu, Dongqing; Lv, Junyuan; Yang, Danli
Abstract: Objectives: Reducing endoplasmic reticulum stress (ERS)-induced cardiomyocyte apoptosis is a key strategy for preventing hypertensive heart disease. In our previous study, Icariside II can improve left ventricular remodelling in spontaneously hypertensive rats (SHRs). This study aims to determine whether Icariside II can exert its effect by inhibiting ERS-induced cardiomyocyte apoptosis via the PERK/ATF-4/CHOP signalling pathway. Methods: Spontaneously hypertensive rats were randomly divided into model group and Icariside II groups. The rats in the Icariside II groups were intragastrically administrated with Icariside II 4, 8 and 16 mg/kg from 14 to 26 week-age, respectively. The left ventricular function was measured at the 18, 22 and 26 week-age by small animal ultrasound. At the end of the 26th week, cardiomyocyte apoptosis was analysed and the levels of GRP78, PERK, ATF-4 and CHOP gene and protein were detected. Key findings: The function of left ventricular became declined with age in SHRs, but improved in Icariside II groups. Myocardial apoptosis was aggravated in SHRs, but alleviated in Icariside II groups. Icariside II could reduce the levels of GRP78, PERK, ATF-4, CHOP gene and protein that increased in SHRs. Conclusions: Icariside II prevents hypertensive heart disease by alleviating ERS-induced cardiomyocyte apoptosis, and its mechanism is related to the impediment of the PERK/ATF-4/CHOP signalling pathway.